Elemen Utama dalam Pembentukan Jati Diri Kesukarelawanan Belia Malaysia - Mohd Mahadee Ismail; Ku Hasnita Ku Samsu; Yok Fee Lee; Marzudi Md Yunus; Khairol Anuar Kamri; Hairol Anuar Mak Din; Mohd Sabri Md Nor; Zatul Himmah Adnan; Nur Shaqirah Md Yunan (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 9 Issue 2 Page (284-294)